Penggunaan Metilprednisolon Sebagai Terapi Sindrom Nefrotik dengan Efusi Pleura pada Anak 16 tahun - Samia Wildana A; Nurifah Nurifah; Sri Hastuti Andayani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Nephrotic syndrome (NS) is a kidney disorder characterized by massive proteinuria, hypoalbuminemia, edema, and hypercholesterolemia, most commonly occurring in children. This disease can be caused by various conditions, such as minimal change disease, FSGS, or lupus nephritis. This case report discusses a 16-year-old boy who experienced nephrotic syndrome with symptoms of swelling throughout his body, accompanied by decreased appetite and a productive cough. The patient presented with complaints of swelling throughout his body that began 7 days after hospitalization and was accompanied by coughing and shortness of breath. A physical examination revealed massive edema, abdominal hypertympany, and shifting dullness. Laboratory tests revealed proteinuria, hypoalbuminemia, and decreased serum albumin. Other supporting tests confirmed nephrotic syndrome. The patient received medication therapy including diuretics, corticosteroids in the form of methylprednisolone, and albumin. Nephrotic syndrome in children can develop gradually and requires management that includes steroids, diuretics, and close monitoring of kidney function and electrolytes. Early detection and appropriate treatment can help improve the patient's prognosis.